2010
DOI: 10.1007/s00436-010-1855-5
|View full text |Cite
|
Sign up to set email alerts
|

Murine schistosomiasis as a model for human schistosomiasis mansoni: similarities and discrepancies

Abstract: Human schistosomiasis has been studied extensively since its discovery by Theodore Bilharz in 1851. Because of its medical importance as a chronic debilitating disease in the tropics and subtropics, continuing research efforts are still going on. The use of animal models still represents a major cornerstone in this field, with murine hosts, especially mice, as the most preferable experimental units. Murine schistosomiasis has been employed as a model for studying various aspects of human schistosomiasis, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…Because mouse model is of high homologization and has similar course with human schistosomiasis, we thus established the mouse schistosomiasis model [41]. In the study, we demonstrated that anti-fibrosis treatment with PZQ significantly improved the hepatic fibrosis of schistosomiasis japonica at both 8 weeks and 15 weeks post-infection, as measured by Sirius Red staining areas and hydroxyproline content.…”
Section: Discussionmentioning
confidence: 91%
“…Because mouse model is of high homologization and has similar course with human schistosomiasis, we thus established the mouse schistosomiasis model [41]. In the study, we demonstrated that anti-fibrosis treatment with PZQ significantly improved the hepatic fibrosis of schistosomiasis japonica at both 8 weeks and 15 weeks post-infection, as measured by Sirius Red staining areas and hydroxyproline content.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, treatment targeting hepatic fibrosis of schistosomiasis remains a challenging proposition [31]. Because the mouse model has a similar course to human schistosomiasis [32], we, thus, established the mouse schistosomiasis model through Schistosoma mansoni cercariae infection, and then treated them with either silymarin alone or plus praziquantel to diminish liver fibrosis in the current study. In this study, all mice received S. mansoni infection in addition to the presence of hepatic granulomas around deposited schistosome eggs affecting hepatocellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, humans are infected for much longer periods than can be modeled in mice. Together, these factors make extrapolation of findings from mouse models to humans difficult (Cheever, 1969;Abdul-Ghani and Hassan, 2010). Until the relevance of these findings for more chronic, lower-level infection in humans can be determined, vigilance should be exerted when treating infected individuals with drugs metabolized by P450s or phase II enzymes.…”
Section: Discussionmentioning
confidence: 99%